Pengembangan LKPD Berbantuan Aplikasi Bookcreator dan Aplikasi Flipbook pada Materi Teks Anekdot pada Siswa Kelas X SMA PAB 8 Saentis - Melani, Siti Eliza; Andriany, Liesna; Ali, Ali (Medan Resource Center, 2025)
This study aims to describe the development process, feasibility, and effectiveness of E-LKPD (Electronic Student Worksheets) assisted by Bookcreator and Flipbook for teaching anecdotal texts to 10th-grade students at SMA PAB 8 Saentis. The research adopts a Research and Development (R&D) methodology following the Thiagarajan 4-D model (Define, Design, Develop, Disseminate). The validation results indicate that the E-LKPD received a 72% feasibility score from content experts (categorized as